Innovative Strategies for Consistent Growth: A Case Study of Southwest Airlines - Mittal , A.K; Sujlana, Paramjit (Gyan Management Journal, 2012)
Southwest Airlines Co. operates Southwest Airlines, a passenger airline, which provides scheduled air transportation throughout the United States. Southwest Airlines is the largest airline measured by number of passengers carried each year within the United States. It is also known as a ’discount airline’ compared with its large rivals in the industry. Rollin King and Herb Kel1eher founded Southwest Airlines on June 18, 1971. The airline began with one simple strategy: "If you get your passengers to their destinations when they want to get there, on time, at the lowest possible fares, and make darn sure they have a good time doing it, people will fly your airline:’ This approach has been the key to Southwest’s success.As of January 2012, Southwest Airlines operates scheduled service to 73 destinations in 38 states and is one of the most honored airlines in the world known for its commitment to the triple bottom line of Performance, People, and Planet. Southwest Airlines provides point-to-point travel destinations. Southwest has 37,000 employees as of January 2012 and operates more than 3,300 flights a day. With a quirky culture and a fleet of more than 500 Boeing 737s, Southwest Airlines has been one of the nation’s few consistently profitable airlines. Southwest Airlines continues to differentiate itself from other low-fare carriers-offering a reliable product with exemplary Customer Service.The U.S. Airline industry lost12.8billion between 1990 and 1994. Southwest was the only airline to be profitable each year during that period. Southwest is the only U.S. Airline to earn a profit every year since 1973.Gary C. Kelly, Chairman of the Board, President, and Chief Executive Officer, Southwest Airlines Co stated, "Despite the decline in earnings, 2011 was a momentous year at Southwest Airlines. We celebrated our 40th year of providing legendary low fare, high quality, and domestic air travel and delivered our 39th consecutive year of profits to our Shareholders. The completely revamped, industry-leading frequent flyer program continues to grow at a strong pace. Results, thus far, are well beyond our expectations."